Thailand and Bangladesh taking policy-level actions to quantify Greenhouse Gas (GHG) emissions and mitigation ambitions in rice based on improved capacity and Measurement, Reporting, and Validation (MRV) supporting tools - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Bangladesh and Thailand demonstrated considerable enhancement in planning and scaling rice-mitigation actions. IRRI-CCAFS’s SECTOR tool played a central role in the design of Thailand’s Rice NAMA which has reached 25,000 households so far, quantifying GHG reduction from rice practices and developing the MRV system. With improvements in GHG emission measurement and successful pilots in the recent years, Bangladesh updated their Nationally Determined Contribution (NDC) with more specifically quantified targets and financial needs for scaling out low-emission rice production practices.